Biological cellulose anti-adhesion material and preparation method thereof
By oxidatively coupled free radicals on biocellulose, inducing in situ graft modification, and introducing cellulase and estrogen, a controlled biodegradable anti-adhesion material was prepared, which solved the biocompatibility and degradation performance problems of existing materials in biomedical applications, and achieved the effect of continuously providing endometrial repair factors and reducing cell adhesion.
Patent Information
- Application Number
- CN202510026626.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-08
AI Technical Summary
Existing anti-adhesion materials have problems with biocompatibility, poor material degradation performance, single function, and insufficient material interface adhesion in biomedical applications, resulting in limited treatment effects and an increased risk of postoperative complications.
In situ grafting N-vinylpyrrolidone modification is initiated by oxidation of biocellulose and nanomicrone needles are used to introduce cellulase and estrogen to prepare a controlled biodegradable anti-adhesion material.
The material has good biocompatibility and controllable degradation performance, can continuously provide biochemical factors required for endometrial repair, and effectively reduce cell adhesion, solving the adhesion problem between the material and tissue interface, improving therapeutic effect and safety.
Smart Images

Figure CN119818737A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomaterials, and specifically relates to a biocellulose anti-adhesion material and a preparation method thereof. Background Art
[0002] Intrauterine adhesions are a gynecological disease that seriously affects women's reproductive health. It is characterized by the formation of fibrous adhesions between the uterine walls due to damage to the endometrial tissue, causing partial or complete occlusion of the uterine cavity. This disease not only has a high incidence rate in women of childbearing age, but also occurs more frequently in high-risk groups such as women who have undergone curettage and recurrent miscarriage or infertility. Intrauterine adhesions can cause patients to experience symptoms such as increased spontaneous abortion rates, decreased menstrual flow or amenorrhea, and also increase the risk of pregnancy complications such as placenta previa and placenta accreta.
[0003] At present, the main clinical approach is to use hysteroscopic adhesion separation combined with estrogen therapy. This approach involves surgical removal of adhesion tissue and the use of estrogen to promote endometrial regeneration. However, this treatment approach carries the risk of inducing secondary adhesions during the healing process of surgical trauma. In order to prevent the re-formation of adhesions, a strategy of implanting anti-adhesion biological scaffold materials to form a physical barrier after surgery is adopted in clinical practice. Although these anti-adhesion materials have achieved certain results in preventing the recurrence of intrauterine adhesions, they still have limitations in many aspects.
[0004] In recent years, biocellulose (BC) has attracted much attention in the biomedical field due to its unique physicochemical properties and good biocompatibility. BC has the characteristics of high purity, high crystallinity, and high mechanical strength. Its biofilm has extremely high water holding capacity and flexibility close to natural tissue, and can adapt to different uterine cavity structures. At the same time, BC has natural biological inertness, which can reduce inflammation and foreign body reaction. By regulating the structure and composition of BC, the controllable degradation of BC scaffolds can be achieved, and its degradation product glucose can be absorbed and utilized by the body without toxic side effects.
[0005] However, there are still the following problems to be solved in the prior art:
[0006] (1) Biocompatibility issues: Some synthetic anti-adhesion materials may cause inflammatory reactions or foreign body reactions, affecting the treatment effect and patient recovery.
[0007] (2) Unsatisfactory material degradation performance: Synthetic anti-adhesion materials lack biodegradability and require secondary surgery to be removed, which can easily cause trauma. The degradation time of some natural materials is uncontrollable, and too fast or too slow will affect the treatment effect. Natural BC cannot be degraded autonomously because the human body lacks a cellulose-degrading enzyme system and needs to be removed after surgery.
[0008] (3) Single function: Most existing barrier materials only have physical isolation effects, lack the biological activity to promote endometrial repair, and cannot actively participate in and regulate the endometrial repair process.
[0009] (4) Material interface problems: The highly hydrophilic surface of natural BC nanofibers results in insufficient adhesion to the uterine wall, affecting its effectiveness as an anti-adhesion barrier.
[0010] These technical defects seriously restrict the effect of anti-adhesion treatment, so it is urgent to develop a new anti-adhesion material that has good biocompatibility, controllable biodegradability, and can actively promote endometrial repair while solving the adhesion problem between the material and the tissue interface. This has important clinical significance for reducing postoperative intrauterine adhesions and reducing the risk of pregnancy complications. Summary of the invention
[0011] In order to solve the above-mentioned defects existing in the current biomaterials for preventing and treating intrauterine adhesions in biomedical applications, the present invention provides a biocellulose anti-adhesion material and a preparation method thereof.
[0012] To achieve the above object, the present invention provides the following technical solutions:
[0013] A method for preparing a biocellulose anti-adhesion material comprises the following steps: in situ grafting of N-vinyl pyrrolidone modification initiated by biocellulose oxidation coupled with free radicals, and then introduction of cellulase and estrogen by nano-microneedles to prepare the biocellulose anti-adhesion material.
[0014] Specifically, the following steps are included:
[0015] (1) TEMPO-catalyzed oxidation: Weigh a biocellulose membrane with a solid content of 5.0%, immerse it in a solution containing TEMPO and NaBr, adjust the pH with NaOH, add 10% sodium hypochlorite solution, place it on a flat shaker, and oxidize it at 25°C;
[0016] (2) In-situ oxidation grafting of N-vinyl pyrrolidone initiated by diradicals: adding ascorbic acid solution to the suspension of biocellulose film catalytically oxidized in step (1), then introducing nitrogen into the reaction vessel and sealing it with a rubber stopper; under nitrogen environment protection, adding 30% hydrogen peroxide solution, a mixed solution of TEMPO and NaBr, and 10% sodium hypochlorite solution, placing the mixture on a flatbed shaker at 37° C. to initiate free radical generation;
[0017] Then, N-vinyl pyrrolidone was added using a syringe, and the reaction vessel was placed in a shaker at 70°C for reaction; after the reaction, the biocellulose membrane was taken out and rinsed with deionized water until the pH of the rinsing solution was neutral and the conductivity was less than 5μS / cm; the washed biocellulose membrane was sterilized by high pressure, washed again, and refrigerated at 4°C for later use;
[0018] (3) Nano-microneedle introduction of cellulase and estrogen: Weigh the composite cellulase and β-estradiol separately, dissolve them in pH 7.4 PBS solution at 4°C, and filter through a 0.2 μm microporous filter membrane for sterilization; load the cellulase and estrogen mixture into a syringe, and use a nano-microneedle introduction instrument to evenly introduce it into the nanofiber membrane; then freeze-dry to obtain a bio-cellulose anti-adhesion material.
[0019] In the step (1), the mass ratio of the active ingredient in the biocellulose membrane to TEMPO is 1:0.02, the mass ratio of the active ingredient in the biocellulose membrane to NaBr is 1:0.1, and the mass ratio of the active ingredient in the biocellulose membrane to 10% sodium hypochlorite solution is 1:7.5. The solid content of the biocellulose membrane is 5.0%; the concentration of NaOH is 0.5M, and the pH is adjusted to 10.5.
[0020] Furthermore, the step (1) is specifically as follows: weighing 100 g of a biocellulose membrane sheet with a solid content of 5.0%, immersing it in 400 mL of a solution dissolved with 0.1 g of TEMPO and 0.5 g of NaBr, adjusting the pH to 10.5 with 0.5 M NaOH, adding 37.5 ml of a 10% sodium hypochlorite solution, placing it on a flat shaker, and oxidizing it at a speed of 20 rpm and 25° C. for 6-24 hours.
[0021] In the step (2), the concentration of the ascorbic acid solution is 0.5 M, the concentration of TEMPO is 50 mM, and the concentration of NaBr is 100 mM.
[0022] Furthermore, the step (2) is specifically as follows: 30 mL of 0.5 M ascorbic acid solution is added to the suspension of the biocellulose film catalytically oxidized in step (1), and then nitrogen is introduced into the reaction container and sealed with a rubber stopper; under nitrogen environment protection, 5 mL of 30% hydrogen peroxide solution, 5 mL of a mixed solution of 50 mM TEMPO and 100 mM NaBr, and 5 mL of 10% sodium hypochlorite solution are added using a syringe, and the mixture is placed on a flat shaker at a speed of 20 rpm and 37° C. to induce free radical generation for 10 minutes; then 5-10 mL of N-vinyl pyrrolidone, place the three-necked flask in a shaking incubator at 70°C and react at a speed of 20rpm for 3-6h; after the reaction, take out the biocellulose membrane and rinse it with deionized water for 30 minutes each time until the pH of the immersion solution is neutral and the conductivity is lower than 5μS / cm; after the washed biocellulose membrane is sterilized at 121°C under high pressure for 30 minutes, it is washed again with medical injection sterile water for 3 times and refrigerated at 4°C for later use.
[0023] In the step (3), the enzyme activity of the composite cellulase is 50 U / mg, the introduction needle of the nano-microneedle introduction instrument is 2.5 mm long, 125 μm in diameter, and the introduction speed is 1.0 mL / min; the freeze-drying conditions are -50°C, 0.1 mbar vacuum, and 72 hours.
[0024] Furthermore, the step (3) is specifically as follows: 400 mg of composite cellulase with an enzyme activity of 50 U / mg and 100 mg of β-estradiol are weighed respectively, dissolved in 10 mL of pH 7.4 PBS solution at 4°C, and sterilized by filtering through a 0.2 μm microporous filter membrane; the cellulase and estrogen mixture is loaded into a syringe, and uniformly introduced into the nanofiber membrane using a nano-microneedle introduction instrument, followed by freeze drying to obtain a biocellulose anti-adhesion material.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The biocellulose anti-adhesion material of the present invention has the characteristics of controlled biodegradation, can continuously provide the biochemical factors required for endometrial repair, and can effectively reduce cell adhesion. The biocellulose anti-adhesion material solves the problems that other synthetic stent materials in the prior art cannot be degraded in the body, causing inflammation or foreign body reaction, resulting in adhesion of the endometrium and the material, causing trauma during separation; and the material itself lacks biological activity and cannot actively participate in and regulate the repair process of the endometrium. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 In the figure, (a) to (e) are the infrared spectra of biocellulose before and after modification, the surface water contact angle, and the elemental analysis results of scanning electron microscope-energy dispersive spectrometer.
[0028] Figure 2 This is the in vitro degradation curve - β-estradiol release curve.
[0029] Figure 3 This is a laser confocal microscopy photo of cell co-culture. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Example 1
[0032] A method for preparing a biocellulose anti-adhesion material, comprising the following specific steps:
[0033] (1) TEMPO-catalyzed oxidation: 100 g of a biocellulose membrane with a solid content of 5.0% (provided by Hainan Guangyu Biotechnology Co., Ltd.) was weighed and immersed in 400 mL of a solution containing 0.1 g of TEMPO and 0.5 g of NaBr, and the pH was adjusted to 10.5 with 0.5 M NaOH. 37.5 mL of 10% sodium hypochlorite solution was added and placed on a flat shaker for oxidation at 20 rpm and 25° C. for 24 h.
[0034] (2) Biradical-induced in-situ oxidation grafting of N-vinylpyrrolidone: Add 30 mL of 0.5 M ascorbic acid solution to the suspension of the biocellulose film catalytically oxidized in step (1) in a three-necked flask, introduce nitrogen for 5 minutes, and seal with a rubber stopper. Under nitrogen environment protection, use a syringe to add 5 mL of 30% hydrogen peroxide solution, 5 mL of a mixed solution of 50 mM TEMPO and 100 mM NaBr, and 5 mL of 10% sodium hypochlorite solution, place on a flat shaker, and initiate free radical generation at a speed of 20 rpm and 37°C for 10 minutes. Then use a syringe to add 10 mL of N-vinylpyrrolidone, place the three-necked flask in a 70°C shaker, and react at a speed of 20 rpm for 6 hours. After the reaction is completed, take out the biocellulose film and rinse it with deionized water for 30 minutes each time until the pH of the leaching solution is neutral and the conductivity is less than 5 μS / cm. The washed biocellulose membrane was sterilized at 121°C for 30 minutes, then washed three times with sterile water for medical injection, and refrigerated at 4°C for later use.
[0035] (3) Nano-microneedle introduction of cellulase and estrogen: 400 mg of composite cellulase with an enzyme activity of 50 U / mg and 100 mg of β-estradiol were weighed, dissolved in 10 mL of pH 7.4 PBS solution at 4°C, and sterilized by filtration through a 0.2 μm microporous filter membrane. The cellulase and estrogen mixture was loaded into a syringe and uniformly introduced into the nanofiber membrane using a nano-microneedle introduction instrument (introduction needle length 2.5 mm, diameter 125 μm, introduction speed 1.0 mL / min). Subsequently, the biocellulose anti-adhesion material was obtained by freeze drying (-50°C, 0.1 mbar vacuum, 72 hours).
[0036] Example 2
[0037] The difference between Example 2 and Example 1 is that the grafting introduction of N-vinyl pyrrolidone in Example 2 only adopts the single free radical initiation grafting mediated by ascorbic acid-hydrogen peroxide, while in Example 1, the in-situ oxidation grafting of N-vinyl pyrrolidone is initiated by both the TEMPO-NaBr-sodium hypochlorite system and the ascorbic acid-hydrogen peroxide system. The specific steps are as follows:
[0038] (1) TEMPO catalytic oxidation: 100 g of a biocellulose membrane with a solid content of 5.0% (provided by Hainan Guangyu Biotechnology Co., Ltd.) was weighed and immersed in a 400 mL solution containing 0.1 g TEMPO and 0.5 g NaBr, and the pH was adjusted to 10.5 with 0.5 M NaOH. 37.5 mL of 10% sodium hypochlorite solution was added and placed on a flat shaker at 20 rpm and 25° C. for 24 hours. After the reaction was completed, the biocellulose membrane was taken out and rinsed with deionized water for 30 minutes each time until the pH of the leaching solution was neutral and the conductivity was less than 5 μS / cm.
[0039] (2) Single free radical-initiated in-situ oxidative grafting of N-vinylpyrrolidone: Add 30 mL of 0.5 M ascorbic acid solution to the suspension of the washed biocellulose membrane in step (1) in a three-necked flask, introduce nitrogen for 5 minutes, and seal with a rubber stopper. Under nitrogen environment protection, use a syringe to add 5 mL of 30% hydrogen peroxide solution, place on a flat shaker, and initiate free radical generation at 20 rpm and 37°C for 10 minutes. Then use a syringe to add 10 mL of N-vinylpyrrolidone, place the three-necked flask on a 70°C shaker, and react at 20 rpm for 6 hours. After the reaction is completed, take out the biocellulose membrane and rinse it with deionized water for 30 minutes each time until the pH of the immersion solution is neutral and the conductivity is less than 5 μS / cm. After the washed biocellulose membrane is sterilized at 121°C for 30 minutes, it is rinsed again with medical injection sterile water for 3 times and refrigerated at 4°C for use.
[0040] (3) Nano-microneedle introduction of cellulase and estrogen: 400 mg of composite cellulase with an enzyme activity of 50 U / mg and 100 mg of β-estradiol were weighed, dissolved in 10 mL of pH 7.4 PBS solution at 4°C, and sterilized by filtration through a 0.2 μm microporous filter membrane. The cellulase and estrogen mixture was loaded into a syringe and uniformly introduced into the nanofiber membrane using a nano-microneedle introduction instrument (introduction needle length 2.5 mm, diameter 125 μm, introduction speed 1.0 mL / min). Subsequently, the biocellulose anti-adhesion material was obtained by freeze drying (-50°C, 0.1 mbar vacuum, 72 hours).
[0041] Example 3
[0042] The difference between Example 3 and Example 1 is that except that the amount of N-vinyl pyrrolidone added is adjusted to 5 mL and the grafting reaction is performed for 3 hours, the other parameters and steps are the same as those of Example 1.
[0043] In order to highlight the beneficial effects of the present invention, the following comparative example experiments are given.
[0044] Comparative Example 1
[0045] Comparative Example 1 is a biocellulose raw material, which is only washed with deionized water for 30 minutes each time until the pH of the washing solution is neutral and the conductivity is less than 5μS / cm, and then sterilized at 121°C for 30 minutes and then washed again with medical injection sterile water for 3 times, and refrigerated at 4°C for use. It is only without any modification or drug loading.
[0046] Comparative Example 2
[0047] Comparative Example 2 Except that TEMPO, NaBr and sodium hypochlorite solution were replaced with equal volumes of deionized water in steps (1) and (2), the remaining steps were the same as those in Example 1. That is, Comparative Example 2 did not perform the TEMPO catalytic oxidation step.
[0048] Comparative Example 3
[0049] Comparative Example 3 is the same as Example 1 except that the N-vinyl pyrrolidone solution is replaced with an equal volume of deionized water in step (2). That is, Comparative Example 3 does not carry out the N-vinyl pyrrolidone grafting reaction step.
[0050] Verification experiment 1: Performance analysis and characterization of biocellulose and its modified materials
[0051] In order to verify the surface modified biocellulose obtained in Examples 1-3 and Comparative Examples 1-3, the N element content and contact angle analysis of the modified materials were performed by scanning electron microscope-energy spectrometer and surface contact angle meter, and the material degradation rate was analyzed by quantitative analysis of residual solids after 14 days of degradation, the release rate was calculated by the ratio of β-estradiol release in 14 days to the initial loading amount, and the adhesion efficiency of fibroblasts NIH 3T3 was evaluated by using a live microscopy counting method after 5 days of co-culture of cellulose materials and cells (with blank control as reference). The results are shown in Table 1:
[0052] Table 1 Performance analysis and characterization of biocellulose and its modified materials
[0053]
[0054] It can be seen from the table that the functional modified biocellulose prepared in Example 1 has a high nitrogen content on the surface and a high water contact angle. After loading cellulase and β-estradiol, it can be controllably degraded and continuously release drugs within a normal intrauterine adhesion treatment cycle of 2 weeks. In addition, the fibroblast adhesion rate on its surface is low, which has an anti-adhesion effect.
[0055] Therefore, the material prepared in Example 1 was further analyzed and characterized, and the results are as follows.
[0056] Verification experiment 2 TEMPO catalytic oxidation-biradical initiated grafting of N-vinyl pyrrolidone characterization and verification
[0057] In order to verify the surface modified biocellulose obtained in Example 1, the material was tested and analyzed using a Fourier transform infrared spectrometer, a surface contact angle meter, and a scanning electron microscope-energy dispersive spectrometer. The results are as follows: Figure 1 shown.
[0058] Compared with the raw biocellulose, the modified biocellulose has a new absorption peak in the infrared spectrum, 1290 cm -1 The -C-N stretching vibration absorption peak of N-vinylpyrrolidone secondary amine is 1650cm -1 The enhanced absorption peak at 1736cm is attributed to the -C==O stretching vibration absorption peak of polyvinyl pyrrolidone and the stretching vibration absorption peak of -COO' introduced into the carboxyl group by TEMPO catalytic oxidation. -1 The stretching vibration absorption peak of carboxyl-COOH was introduced for TEMPO-catalyzed oxidation. Thus, N-vinyl pyrrolidone was successfully introduced on the surface of biocellulose through TEMPO-catalyzed oxidation and free radical-initiated polymerization.
[0059] From the analysis of the water contact angle of the material surface, it can be seen that after the introduction of N-vinyl pyrrolidone on the cellulose surface, the water contact angle increased significantly. Compared with the hydrophilic biocellulose surface, the hydrophobicity of the modified biocellulose surface increased, which can reduce the adhesion of cells on the surface and lay the foundation for the anti-adhesion performance of the material.
[0060] From the SEM analysis of the surface morphology of the material, it can be seen that the surface of the biocellulose before modification is an ultra-fine fiber network structure with a rough and porous surface. Although the surface of the material has a wrinkled structure after modification, the surface is smooth, which can reduce cell adhesion and prevent tissue adhesion during application. Through the analysis of the C, N, and O element content of the material surface by an energy spectrometer, it can be seen that the surface of the biocellulose contains 1.26% nitrogen, which comes from the bacterial protein or nucleic acid remaining in the membrane. The nitrogen element on the surface of the cellulose material increased significantly after modification, which once again verified the successful introduction of N-vinyl pyrrolidone on the cellulose surface.
[0061] Verification experiment 3: Nano-microneedle introduction of cellulase and estrogen verification
[0062] To verify the introduction of cellulase and estrogen by nano-microneedles in Example 1, 100 mg of the prepared material was weighed and placed in a 6-well cell culture plate. 5 mL of PBS solution was added and placed on a flat shaker. The plate was incubated at 20 rpm and 37 degrees Celsius. During the incubation process, samples were taken at intervals of 12 hours for photographing and testing. The samples were taken out and centrifuged at 5000 rpm for 5 minutes. The absorbance of the supernatant was detected at 280 nm. The release rate of β-estradiol loaded in the material was calculated based on the β-estradiol absorbance standard curve and the amount of β-estradiol loaded by the microneedles. After the sample was centrifuged, the supernatant was aspirated, and the solid sample was transferred to a 105°C oven and dried to constant weight. The degradation rate of the material was calculated based on the initial sample weight. Under the same conditions, the same mass of unmodified biocellulose was taken as a control for testing. The results are as follows Figure 2 shown.
[0063] It can be seen from the degradation curve that the unmodified bio-cellulose has no significant mass loss after 14 days of incubation due to the lack of cellulose degrading enzymes. The mass loss of about 1% from 7 to 14 may come from the collapse of the edge structure of the material. In contrast, the mass loss rate of the material prepared in the example gradually increases with the extension of the incubation time, and gradually tends to equilibrium after 10 days. At the same time, the overall structure of the material begins to become thinner and gradually collapses from the 7th day, and is basically completely broken after 12 days. It can be seen that the material prepared by this method can destroy the material structure under the degradation action of the cellulase embedded in itself, thereby solving the problem that the bio-cellulose material cannot be degraded autonomously in the body.
[0064] It can be seen from the β-estradiol release curve that the β-estradiol released by the material prepared in the embodiment shows a rapid release in the first 7 days as the incubation time is prolonged, and then a slow and lasting release reaches equilibrium within 7-12 days. The rapid release of β-estradiol in the first 7 days is attributed to partial surface adsorption and microneedle introduction of shallow β-estradiol release. At the same time, with the degradation of the material and the collapse of the structure, the β-estradiol loaded in the deep layer is continuously released. After incubation for 14 days, the β-estradiol release rate can reach 97%, which has a good loading and release capacity. The released estrogen is expected to provide a stable and continuous biomolecular signal for endometrial repair, thereby achieving the goal of actively participating in and regulating endometrial repair.
[0065] Validation experiment 4: Validation of the anti-adhesion potential and immune safety of biocellulose
[0066] In order to verify the anti-adhesion potential and immune safety of the biocellulose prepared in Example 1, the prepared material was co-cultured with fibroblasts NIH 3T3 and macrophages Raw 264.7, and the cell adhesion and growth status were analyzed by immunofluorescence staining and laser confocal microscopy imaging after 5 days of culture. Figure 3 shown.
[0067] It can be seen from the laser confocal microscopy image of macrophage growth that after co-culture of biocellulose and the biocellulose anti-adhesive material prepared in the embodiment with macrophages for 5 days, the macrophages grew well and showed the same cell morphology as the blank control. No pro-inflammatory polarization or anti-inflammatory polarization was observed in the cells, indicating that the material does not cause inflammatory response and does not have anti-inflammatory function, and is an immunologically inert material. At the same time, the normal growth of macrophages indicates that the material has no cytotoxicity and has good biocompatibility.
[0068] From the laser confocal microscopy image of fibroblast growth, it can be seen that the fibroblasts are almost completely adhered and covered on the surface of the unmodified biocellulose, and the cell growth state is good. The surface of the unmodified biocellulose has no anti-adhesion effect. In contrast, only a small amount of cells adhere and grow on the surface of the biocellulose anti-adhesion material prepared in the example, and the cytoskeleton structure fails to fully spread out, indicating that the material has a good anti-adhesion effect.
[0069] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a biocellulose anti-adhesion material, characterized in that: The biocellulose anti-adhesion material was prepared by in-situ grafting of N-vinylpyrrolidone via free radical-initiated oxidation of biocellulose and then introduction of cellulase and estrogen into the nano-microneedles.
2. The method for preparing the biocellulose anti-adhesion material according to claim 1, characterized in that: The following steps are involved: (1) TEMPO-catalyzed oxidation: Weigh a biocellulose membrane with a solid content of 5.0%, immerse it in a solution containing TEMPO and NaBr, adjust the pH with NaOH, add 10% sodium hypochlorite solution, place it on a flat shaker, and oxidize it at 25°C; (2) In-situ oxidation grafting of N-vinyl pyrrolidone initiated by diradicals: adding ascorbic acid solution to the suspension of biocellulose film catalytically oxidized in step (1), then introducing nitrogen into the reaction vessel and sealing it with a rubber stopper; under nitrogen environment protection, adding 30% hydrogen peroxide solution, a mixed solution of TEMPO and NaBr, and 10% sodium hypochlorite solution, placing the mixture on a flatbed shaker at 37° C. to initiate free radical generation; Then, N-vinyl pyrrolidone was added using a syringe, and the reaction vessel was placed in a shaker at 70°C for reaction; after the reaction, the biocellulose membrane was taken out and rinsed with deionized water until the pH of the rinsing solution was neutral and the conductivity was less than 5μS / cm; the washed biocellulose membrane was sterilized by high pressure, washed again, and refrigerated at 4°C for later use; (3) Nano-microneedle introduction of cellulase and estrogen: Weigh the composite cellulase and β-estradiol separately, dissolve them in pH 7.4 PBS solution at 4°C, and filter through a 0.2 μm microporous filter membrane for sterilization; load the cellulase and estrogen mixture into a syringe, and use a nano-microneedle introduction instrument to evenly introduce it into the nanofiber membrane; then freeze-dry to obtain a bio-cellulose anti-adhesion material.
3. The method for preparing the biocellulose anti-adhesion material according to claim 2, characterized in that: In the step (1), the mass ratio of the active ingredient in the biocellulose membrane to TEMPO is 1:0.02, the mass ratio of the active ingredient in the biocellulose membrane to NaBr is 1:0.1, and the mass ratio of the active ingredient in the biocellulose membrane to 10% sodium hypochlorite solution is 1:7.
5.
4. The method for preparing the biocellulose anti-adhesion material according to claim 3, characterized in that: In the step (1), the solid content of the biocellulose membrane is 5.0%; the concentration of NaOH is 0.5M, and the pH is adjusted to 10.
5.
5. The method for preparing the biocellulose anti-adhesion material according to claim 4, characterized in that: Specifically, the step (1) comprises weighing 100 g of a biocellulose membrane sheet having a solid content of 5.0%, immersing the sheet in 400 mL of a solution containing 0.1 g of TEMPO and 0.5 g of NaBr, adjusting the pH to 10.5 with 0.5 M NaOH, adding 37.5 mL of a 10% sodium hypochlorite solution, placing the sheet on a flat shaker, and oxidizing the sheet at a speed of 20 rpm and 25° C. for 6-24 hours.
6. The method for preparing the biocellulose anti-adhesion material according to claim 2, characterized in that: In the step (2), the concentration of the ascorbic acid solution is 0.5 M, the concentration of TEMPO is 50 mM, and the concentration of NaBr is 100 mM.
7. The method for preparing the biocellulose anti-adhesion material according to claim 6, characterized in that: The step (2) is specifically as follows: 30 mL of 0.5 M ascorbic acid solution is added to the suspension of the biocellulose film catalytically oxidized in step (1), and then nitrogen is introduced into the reaction container and sealed with a rubber stopper; under nitrogen environment protection, 5 mL of 30% hydrogen peroxide solution, 5 mL of a mixed solution of 50 mM TEMPO and 100 mM NaBr, and 5 mL of A 10% sodium hypochlorite solution was placed on a flat shaker, and free radical generation was initiated at 20 rpm and 37°C for 10 minutes; 5-10 mL of N-vinyl pyrrolidone was then added using a syringe, and the three-necked flask was placed on a 70°C shaker, and reacted at 20 rpm for 3-6 hours; after the reaction, the biocellulose membrane was taken out and rinsed with deionized water for 30 minutes each time until the pH of the immersion solution was neutral and the conductivity was less than 5 μS / cm; the washed biocellulose membrane was placed in an autoclave at 121°C for 30 minutes, and then rinsed again with medical injection sterile water for 3 times, and refrigerated at 4°C for later use.
8. The method for preparing the biocellulose anti-adhesion material according to claim 2, characterized in that: In the step (3), the enzyme activity of the composite cellulase is 50 U / mg, the introduction needle of the nano-microneedle introduction instrument is 2.5 mm long, 125 μm in diameter, and the introduction speed is 1.0 mL / min; the freeze-drying condition is -50°C, 0.1mbar vacuum, 72 hours.
9. The method for preparing the biocellulose anti-adhesion material according to claim 8, characterized in that: The step (3) specifically comprises: weighing 400 mg of composite cellulase with an enzyme activity of 50 U / mg and 100 mg of β-estradiol, respectively, dissolving them in 10 mL of pH 7.4 PBS solution at 4° C., and filtering and sterilizing them through a 0.2 μm microporous filter membrane; loading the cellulase and estrogen mixture into a syringe, and uniformly introducing them into the nanofiber membrane using a nano-microneedle introduction instrument, followed by freeze-drying to obtain a biocellulose anti-adhesion material.
10. The biocellulose anti-adhesion material obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for preparing cellulose acetate graft polymer from cellulose according to one-pot method
CN104072673A
Biological anti-adhesion repairing auxiliary material and preparation method thereof
CN109621016A
Construction method and application of cell growth factor slow-release anisotropic scaffold based on nanocellulose
CN112138215A
Minimal tissue attachment implantable materials
US20100159046A1
Adhesion prevention agent comprising injectable thermosensitive wood based-oxidized cellulose nanofiber
US20190015564A1